Conveying glycan information into T-cell homeostatic programs: a challenging role for galectin-1 in inflammatory and tumor microenvironments - Rabinovich, Gabriel Adrián (2009)
The immune system has evolved sophisticated mechanisms composed of several checkpoints and fail-safe processes that enable it to orchestrate innate and adaptive immunity, while at the same time limiting aberrant or unfaithful T-cell function. These multiple regulatory pathways take place during the entire life-span of T cells including T-cell development, homing, activation, and differentiation. Galectin-1, an endogenous glycan-binding protein widely expressed at sites of inflammation and tumor growth, controls a diversity of immune cell processes, acting either extracellularly through specific binding to cell surface glycan structures or intracellularly through modulation of pathways that remain largely unexplored. In this review, we highlight the discoveries that have led to our current understanding of the role of galectin-1 in distinct immune cell process, particularly those associated with T-cell homeostasis. Also, we emphasize findings emerging from the study of experimental models of autoimmunity, chronic inflammation, fetomaternal tolerance, and tumor growth, which have provided fundamental insights into the critical role of galectin-1 and its specific saccharide ligands in immunoregulation. Challenges for the future will embrace the rational manipulation of galectin-1-glycan interactions both towards attenuating immune responses in autoimmune diseases, graft rejection, and recurrent fetal loss, while at the same overcoming immune tolerance in chronic infections and cancer.